Sanksi Pidana terhadap Kecurangan dalam Laporan Dana Kampanye Pemilihan Umum di Indonesia - Ni Nyoman Sonia Santhy Suryani; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2022)
In 2019, Dr Somvir, a legislative candidate for Bali Regional People’s Representative Council, reported his campaign fund was zero rupiah, which was later reported to Election Supervisory Body Bali as a case of suspicion of fraud in the campaign fund report. The fraud was manipulating the number of campaign funds received or used. The purpose of this study is to discuss the legal arrangements regarding general election campaign finance reports in Indonesia and to examine the criminal sanctions imposed on fraud in general election campaign finance reports in Indonesia. The research method and problem approach used is a normative method with a conceptual and statutory approach. The results of this study explain campaign fund report is regulated on Law Number 7 of 2017 about General Election and Regulation by General Election Commission Number 24 of 2018 about Campaign Fund in General Election. Criminal sanctions for fraud in campaign fund reports in the Indonesian general election could be confinement, imprisonment, and fines, which are regulated on Article 496 and 497 Law Number 7 of 2017. The government needs to explain clearly the meaning of information in campaign fund reports in the general elections.